The COVID-19 Pandemic and Scientific Community Response in France, Greece, Norway, and Spain - Medard, Maxime; Perraud, Sarah; Utrilla Sanchez, Andrea; Gonzalez Tornos, Paula; Yogendran, Dilani; Chaleplioglou, Artemis (Journal of Integrated Information Management, 2023)
Purpose – COVID-19 pandemic claimed millions of lives and changed everyday life for billions of people worldwide. Europe was severely impacted in health, social and economic aspects. Research efforts reallocation was a necessity to battle against this threat. Design/methodology/approach – The scientific community responses against COVID-19 were assessed in terms of country paper productivity indexed in PubMed, Scopus, Web of Science, Dimensions and iCite databases. This research project was designed and performed in the framework of Health Information and Libraries Erasmus+ course with the participation of information science students from France, Norway, and Spain. Findings – Prior to COVID-19 emergence, coronaviruses related publications accounted for approximately 0.15% of the total research output of more than 800,000 reports affiliated to France, Greece, Norway, or Spain. After COVID-19 pandemic the related scientific output was increased by 60-times to a 7% of the total scientific output of more than 900,000 affiliated reports. Between 2020 and 2022, 21,299 COVID-19 publications were affiliated to France, 6897 to Greece, 5353 to Norway, and 29,195 to Spain accounted collectively for approximately 9% of the global scientific output. The coronavirus related publications involved Medicine, Immunology and Microbiology, Biochemistry, Genetics and Molecular Biology but also humanities and social sciences, and economics and business. Originality/value - COVID-19 spread fast across the globe from Asia to Europe despite quarantines and social distancing measures. International collaborations, space and funding reallocation led to an enormous original research output within months. Lessons from these responses are invaluable in future pandemic preparedness.